Conflict and Poverty - Mueller, Hannes; Techasunthornwat, Chanon (World Bank, Washington, DC, 2020)
This paper analyzes the relationship between poverty and conflict in the macro and regional data, including a detailed case study of Uganda. The paper relies on a large and growing literature that provides evidence on the devastating impact that conflict has on health and expectations. Based on this evidence, it develops a statistical framework to track the cumulative long-term impact that armed conflict has on poverty, which the paper calls conflict debt. The data confirm that contemporaneous conflict leads to a conflict debt which is only recovered slowly. The empirical model is not only a good description of the cross-country aggregate poverty time-series data, but also regional cross-sectional data. A new aspect in the model is that armed conflict can prevent poverty reduction and, once it is over, allow for strong catch‐up effects as they exist in the data. But in the most conflict-ridden countries, repeated cycles of violence prevent poverty from recovering. According to the most conservative estimates, these countries and regions would have 5‐10 percentage points lower poverty rates without their conflict debt.